2016
DOI: 10.1103/physrevlett.117.165101
|View full text |Cite
|
Sign up to set email alerts
|

Rippled Quasiperpendicular Shock Observed by the Magnetospheric Multiscale Spacecraft

Abstract: Collisionless shock nonstationarity arising from microscale physics influences shock structure and particle acceleration mechanisms. Nonstationarity has been difficult to quantify due to the small spatial and temporal scales. We use the closely spaced (subgyroscale), high-time-resolution measurements from one rapid crossing of Earth's quasiperpendicular bow shock by the Magnetospheric Multiscale (MMS) spacecraft to compare competing nonstationarity processes. Using MMS's high-cadence kinetic plasma measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
119
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 27 publications
12
119
1
Order By: Relevance
“…Individual normals deviated from the timing analysis normal by up to 30°. This is presumably a typical feature of high Mach number shocks, in agreement with several past modeling studies of shocks (Burgess, ; Burgess & Scholer, ; Lowe & Burgess, ; Ofman & Gedalin, , ; Winske & Quest, ) as well as observations reported by (Johlander et al, ). In particular, Ofman and Gedalin (, ) discussed the deviation of the shock normal due to rippling, based on their 2‐D hybrid simulation study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Individual normals deviated from the timing analysis normal by up to 30°. This is presumably a typical feature of high Mach number shocks, in agreement with several past modeling studies of shocks (Burgess, ; Burgess & Scholer, ; Lowe & Burgess, ; Ofman & Gedalin, , ; Winske & Quest, ) as well as observations reported by (Johlander et al, ). In particular, Ofman and Gedalin (, ) discussed the deviation of the shock normal due to rippling, based on their 2‐D hybrid simulation study.…”
Section: Discussionsupporting
confidence: 91%
“…To conclude, we present the results of a comparative study of two quasi‐perpendicular collisionless shocks in the solar wind, with low (IP shock) and high (bow shock) Mach number: The cross‐shock NIF potential from electric field measurements is 24–28 V for the IP shock (with 41–42 V from the electron proxies), and 290–440 V for the bow shock (with 240–260 V from the electron proxies). The ion proxies cannot be used for high Mach number shocks because the ion moments are spoiled by reflected ions before and during the ramp. The low Mach number IP shock surface was almost planar on the scale of the MMS spacecraft configuration as well as on the scale of the MMS and ARTEMIS separation distance (~20 R E ). The high Mach number bow shock surface was rippled on the scale of the MMS spacecraft configuration, in agreement with the results of Burgess (), Burgess and Scholer (), Lowe and Burgess (), Ofman and Gedalin (, ), and Winske and Quest () and the observations of Johlander et al (). …”
Section: Discussionmentioning
confidence: 99%
“…But also during rather stable conditions, it can be both nonuniform and nonstationary. For example, ripples can propagate on the surface and it has been suggested that the shock can exhibit cyclical reformation (e.g., Auer et al, ; Eastwood et al, ; Johlander et al, ). As shown in section 3, the events included in our database are observed Earthward of the nominal subsolar position of the bow shock, indicating that they correspond to rather elevated upstream solar wind conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This is especially important in regions for which kinetic plasma processes are significant, and associated nongyrotropic particle populations are common. The MMS mission targets several of these regions, such as the bow shock (Johlander et al, ) or the diffusion regions of magnetic reconnection sites (Burch, Torbert, et al, ). In these regions, characterization of the full ion or electron phase space is critical to understanding of microphysics processes.…”
Section: Introductionmentioning
confidence: 99%